Concentrations of oocyte secreted GDF9 and BMP15 decrease with MII transition during human IVM - Jesús Cadenas; Susanne Elisabeth Pors; Ajay Kumar; Bhanu Kalra; Stine Gry Kristensen; Claus Yding Andersen; Linn Salto Mamsen (BMC, 2022)
Abstract Background The suggested effects of the oocyte secreted GDF9 and BMP15 growth factors on oocyte maturation are currently based on recombinant proteins, and little is known about native GDF9 and BMP15 in humans. Methods Human immature cumulus-oocyte complexes (COCs) obtained in connection with ovarian tissue cryopreservation (OTC) underwent in vitro maturation (IVM). Oocyte-produced GDF9 and BMP15 were detected in COCs using immunofluorescence, and in fresh GV oocytes and in GV and MII oocytes after IVM by western blot. Concentrations of GDF9, BMP15 homodimers, and GDF9/BMP15 heterodimer in spent media after IVM were measured by ELISA. The relative expression of seven genes from the GDF9 and BMP15 signaling pathways (BMPR2, ALK5, ALK6, SMAD1, SMAD2, SMAD3, and SMAD5) was evaluated in fresh cumulus cells (before IVM) and in cumulus cells from GV and MII oocytes after IVM by RT-qPCR. Results We detected native pro-mature GDF9 and BMP15 in human oocytes with molecular weights (Mw) of 47 kDa and 43 kDa, respectively. Concentrations of GDF9 and BMP15 in spent media after IVM were detected in 99% and 64% of the samples, respectively. The GDF9/BMP15 heterodimer was detected in 76% of the samples. Overall, the concentration of GDF9 was approximately 10-times higher than BMP15. The concentrations of both GDF9 and BMP15 were significantly lower in spent medium from MII oocytes than in media from oocytes that remained at the GV stage. Concentrations of the GDF9/BMP15 heterodimer did not differ between GV and MII oocytes. Furthermore, BMPR2, SMAD3, and SMAD5 were significantly upregulated in cumulus cells from MII oocytes, indicating that both GDF9 and BMP15 signaling were active during oocyte meiotic resumption in vitro. Conclusion These data suggest that the driving mechanisms for oocyte nuclear maturation may involve both GDF9 and BMP15 homodimers, while the role of the GDF9/BMP15 heterodimer is questionable.